2004
DOI: 10.1021/ac0494580
|View full text |Cite
|
Sign up to set email alerts
|

Micromixing with Linked Chains of Paramagnetic Particles

Abstract: Paramagnetic colloidal particles aggregate into linear chains under an applied external magnetic field. These particles can be chemically linked to create chains that can be magnetically actuated to manipulate microscopic fluid flow. The flexibility of the chain can be adjusted by varying the length of the linker molecule. In this paper, we describe the use of a suspension of linked paramagnetic chains in a rotating magnetic field to perform microscale mixing. The effect of chain rotation and flexibility on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 25 publications
3
144
0
Order By: Relevance
“…Indeed, the degradation of 4-nitrophenol and methylene blue proceeds considerably faster in the microdroplets than in the conventional container under the same magnetic field conditions. This is in concordance with the results obtained with composite microstirrers, which were demonstrated to efficiently enhance the catalysis of diverse types of reactions in microdroplet conditions [32,33].…”
Section: Role Of the Reaction Geometrysupporting
confidence: 90%
“…Indeed, the degradation of 4-nitrophenol and methylene blue proceeds considerably faster in the microdroplets than in the conventional container under the same magnetic field conditions. This is in concordance with the results obtained with composite microstirrers, which were demonstrated to efficiently enhance the catalysis of diverse types of reactions in microdroplet conditions [32,33].…”
Section: Role Of the Reaction Geometrysupporting
confidence: 90%
“…Superparamagnetic (SPM) beads have proven to be a highly efficient materials for separating proteins, nucleic acids, viruses, and cells, due to the high surface area, and the high rate of 20 separation and mass transfer that takes place in highly concentrated suspensions of micron size beads. [1][2][3][4][5] For example, antibody and glass functionalized SPM beads are now widely used for the isolation of specific cell types and nucleic acids, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5,[17][18][19][20][21] This has limited HGM to dilute solutions in which bead-bead interaction are unlikely to occur. FEM calculations of the local magnetic field on the MMAs, as shown in Figure 1B, revealed that the SPM beads produce little change in the local magnetic field and thus the SPM beads do not interact with each other to 5 form chains.…”
Section: Introductionmentioning
confidence: 99%
“…Of important note is the assembly process is a reversible one; as the field is switched off, the clusters will disassemble, turning off device function if desired. One significant advantage of the colloids we use here is that they are readily available with a variety of surface functionalities, including reactive groups that can be used for irreversible assembly binding (19) if continued device operation is useful after field switch-off. And although only 2 of these valves are shown, their construction could be performed in a parallel fashion because of the global nature of the driving field.…”
Section: Resultsmentioning
confidence: 99%